Analisis Pendapatan Dan Kelembagaan Dalam Mendukung Peningkatan Posisi Tawar Petani Kelapa Sawit Rakyat Di Kabupaten Deli Serdang Sumatera Utara - Nainggolan, Hotden Leonardo; Albina Ginting; Jongkers Tampubolon (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
The purpose of this study was to analyze income and institutions in supporting the improvement of the bargaining position of smallholder oil palm farmers. This study was conducted from June to October 2024. The research sample was 30 samples determined purposively. This study used primary and secondary data and was analyzed descriptively qualitatively. Based on the results of the study, it was concluded; a) the income of smallholder oil palm farmers in the research area was IDR 2,560,645/month; b) the existing condition of smallholder oil palm farming institutions is reflected in the existence of; farmers as farm managers, farmer groups, farmer group associations, farmer associations, palm oil processing industries, financing institutions, extension institutions; c) Farming institutions play a role in the development of smallholder oil palm farming, as a social institution and supporting farming; d) Institutions play a role in extension activities and function as economic institutions; e) institutions play a role as information services and act as providers of regional infrastructure services; e) institutions play a role as distribution access to markets and sources of capital for farmers to develop farming businesses. Based on the results of the study, it is recommended that the government provide extension and training to smallholder oil palm farmers to improve their understanding of the role of institutions in developing sustainable smallholder oil palm farming businesses so that they can improve the bargaining position of smallholder oil palm farmers. Keywords: bargaining position; farmers; institutions, smallholder oil palm.